A vida cotidiana no movimento das águas pantaneiras - Luiz, George Moraes de (2015)
This research looks into the co-inhabitance of the population native to the Pantanal region in the center-west region of Brazil, state of Mato Grosso, with the cycle of full tide of the swamps surrounding the rural areas of three cities. We have selected the water cycle as our subject because they dictate the course all forms of life in the Pantanal. The basis of our discussion is formed by an interdisciplinary perspective, which allows for theoretical and methodological approximations with different areas of the social sciences and human sciences, notably the theoretical and epistemological notions of the Actor-Network theory. This has provided us with the understanding of the swamps as heterogeneous networks, establishing a debate with authors of the field of Environmental Education. We have assigned ourselves the task of writing a thesis in which both style and content question the "canons" of the academy, thus opening ourselves to reflections upon new manners of doing social research. In this challenge, we have given a poetic note to the text, valuing the traditional knowledge of the Pantanal region without losing sight of scientific knowledge. This thesis is the result of experiences lived by the researcher as an inhabitant of the Pantanal region, as wells as a result of formal and informal conversations with 42 people who are directly associated with the activities conducted in the swamps, among whom those who live on the river banks. Anchored in the notions of Everyday Conversation, with semi-structured script and field annotations, we have systematized the information by the means of fluctuating readings, generating themes which comprise the corpus of the thesis in the form descriptive narratives. The focus of our analysis is on the manner in which traditional populations predict, prepare themselves for, and live with the cycle of full tide, prioritizing the association between humans and non-humans as a possibility for survival in a flooded territory. The co-inhabitance of people with the full tides is described here in three different themes: birth-giving, housing, and means of transportation. This way of life, intertwined with nature, is commonly described in classic literature as the culture and tradition of the Pantanal populations. However, what we indicate here is that new actors, such as the construction of river dams, park roads and industrial plants, interfere in the Pantanal, altering the cycle of full tide. Due to this interference, it becomes unviable to understand the ways of life of the local populations as crystallized, which makes us argue in favor of the processuality of relations between people and nature, while rethinking the very notion of what the swamps come to be after constant socio-environmental interventions